2017
DOI: 10.3389/fneur.2017.00278
|View full text |Cite|
|
Sign up to set email alerts
|

The Effect of Systemic Nitroglycerin Administration on the Kynurenine Pathway in the Rat

Abstract: The primary headache disorders include migraine, which is one of the most frequent neurological disorders, which influences more than 14% of the whole population. Despite the research efforts, its exact pathomechanism is not fully revealed, but evidence points to the role of glutamate and its receptors. Kynurenic acid is an endogenous glutamate receptor antagonist produced by the kynurenine pathway (KP). Tryptophan 2,3-dioxygenase (TDO) and indoleamine 2,3-dioxygenase (IDO) convert l-tryptophan to N-formyl-l-k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 31 publications
1
15
0
Order By: Relevance
“…It has been hypothesized that kynurenines could play a role in migraine by modulating glutamatergic activity [17]. In animal models of migraine, nitroglycerine downregulates the kynurenine pathway [18] while kynurenines have been shown to reduce nitroglycerinevoked hyperalgesia [19] and cortical spreading depression [20]. Altered levels of kynurenines have been reported in chronic migraine patients [21].…”
Section: Endogenous Glutamate Receptor Modulators In Migrainementioning
confidence: 99%
“…It has been hypothesized that kynurenines could play a role in migraine by modulating glutamatergic activity [17]. In animal models of migraine, nitroglycerine downregulates the kynurenine pathway [18] while kynurenines have been shown to reduce nitroglycerinevoked hyperalgesia [19] and cortical spreading depression [20]. Altered levels of kynurenines have been reported in chronic migraine patients [21].…”
Section: Endogenous Glutamate Receptor Modulators In Migrainementioning
confidence: 99%
“…In this model, NTG was able to decrease the expression of kynurenine aminotransferase II (KATII) [ 45 ], which is the key enzyme of KYNA production. In a recent study, it was also shown that NTG altered the expression of other enzymes of the KP, namely TDO, IDO, KYNU and KMO, suggesting that NTG/NO has an influence on the KP [ 46 ].…”
Section: Kynurenine Pathway (Kp) and Migrainementioning
confidence: 99%
“…Moreover, Rojewska, Ciapala, Piotrowska, Makuch, and Mika () found that IDO2 and KMO may be the new treating targets for neuropathic pain. Nagy‐Grocz et al () also found that the mechanism of nitroglycerin on treating primary headache may be related to KP regulated by KMO. NMDAR is an important intermediate substrate for KMO treatment of ischemic stroke, and the upstream product IDO of KMO is also a problem worthy of study.…”
Section: The Mechanism Of Kmo In Different Diseasesmentioning
confidence: 97%